Voter Behavior in The Regional Head Election at Blora Regency in Pandemic Era Year 2020 - Rupiarsieh, M. Si (Advances in Social Sciences Research Journal, 2022)
Covid-19 pandemic, destroy all aspect of social and state life, including political process in the election of Regional Head. Many peoples doubt the regional head election can be done well. They think peoples will ignore the Democratic process in pandemic situation. The lack of preparation of the organizers to the unpreparedness of the election officers. Many peoples were still afraid to leave their house, because the pandemic situation was getting worst. Moreover, there were PKPU No. 13 Year 2020, which prohibits any form of campaign or other physical activity, and must be carried out using media or online. In other side, voter participation at Blora Regency in year 2020, instead of decreasing, but actually increasing, from 71.61 % to 77,47 % compared to 2015 Regional Head Elections. It is very interesting condition to research of voter behavior on Regional Head Election at Blora Regency in year 2020. This study will use the quatitavie approach to get the data by interview and survey from The Election Commission, the political party leader, public figure and the candidat. The data is also taken from related documents. Based on the theory and the result of this study, it shows that the increase of voter participation, because the people who live in Blora Regency or those who return home to Blora, are in jobless condition in pandemic condition. They can use the right to vote. The voter behavior is match with sosiological of voter behavior, as a result of pandemic condition and political condition. The goverment policies of Enforcement of Restrictions on Community Activities has impact to economic factors. It makes the economic life is very hard. This external factors influence the peoples to use their righrt to vote. In pandemic situation the jobless peoples get donations through the election activity. The novelty of this study is external factors that comes suddenly. This situation can change the voter behavior to use they right to vote, according to who is able toalleviate their economic needs. And the sociological approach of this study is depend on family factors, religion, the same political party. It is an acquired preference for long time.